Cutaneous leishmaniasis in the 21st century: from the laboratory to the bedside. Issue 5 (October 2019) - Barkati, Sapha; Ndao, Momar; Libman, Michael
Abstract : Purpose of review: Despite modern advances in molecular diagnostic tools and a better understanding of its complex pathophysiology, cutaneous leishmaniasis, a neglected tropical disease, remains a major global health problem. Laboratory methods to inform prognosis and treatment are not widely available, the therapeutic options are limited and have significant adverse effects, and emergence of drug resistance is a further complication. New advances in the understanding of the role of Leishmania RNA virus (LRV) as a prognostic factor, speciation methods and antimicrobial resistance testing and their limitations will be discussed. Recent findings: LRV, an intracytoplasmic endosymbiont found mostly in Leishmania spp. associated with more severe disease, appears to play a role in modulating the host immune response and has been associated with treatment failure in some Viannia subgenus species. Proper speciation is an important guide to management. However, recent findings have demonstrated significant heterogeneity of results related to differences in genotyping methods. Summary: Recognition of the role of LRV in immune modulation and response to treatment along with more accessible tools for its detection to guide management at the bedside should allow a better individualized approach. Improving accessibility and standardization of speciation methods and antimicrobial susceptibility testing should be major goals to improve cutaneous leishmaniasis management in the 21st century.